The Effect of Mathematical Problem-Solving on Mathematical Literacy and Its Implications for Islamic Financial Literacy - Muniri; Wahyu Dwi Warsitasari; Nurul Laili; Savera Eka Ardita (Lattice Journal : Journal of Mathematics Education and Applied, 2026)
The impact of mathematical problem-solving skills on mathematical literacy and its consequences for Islamic financial literacy among undergraduate students enrolled in Islamic Economics programs in East Java, Indonesia, are examined in this study. 385 students from three Islamic institutions were surveyed as part of a quantitative method employing multistage sampling. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to analyze the data. The findings demonstrate that whereas mathematics literacy strongly impacts Islamic financial literacy, problem-solving skills have a considerable beneficial impact on mathematical literacy. However, problem-solving ability does not have a direct or indirect significant effect on Islamic financial literacy. These findings indicate that mathematical literacy acts as a key cognitive bridge, although its role in Islamic financial literacy remains limited without contextual integration of financial knowledge. The model demonstrates stronger explanatory power for mathematical literacy compared to Islamic financial literacy, suggesting the presence of additional unobserved factors influencing financial literacy outcomes. The study concludes that Islamic financial literacy is not solely determined by mathematical competence but requires contextualized learning that integrates mathematical reasoning with Islamic financial concepts and financial behavioral exposure.